Survey on Vietnam - Korea Trade Situation after VKFTA (2015-2020): Achievements and Issues - Nguyen Thi Thu Huong,; Le Thi Thu, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
After officially establishing diplomatic relations in 1992, trade relations between Vietnam and Korea have been increasingly consolidated and developed with many important agreements being signed. The Vietnam - Korea Free Trade Agreement (VKFTA) applied from the end of 2015 is expected to create an important turning point, supporting the two countries' trade growing stronger and deeper. In fact, after 5 years of applying VKFTA, based on the background of similarities and differences, Vietnam - Korea trade exchange has continuously developed in many fields with impressive outcomes. The objectives of the presentation are: (1) to study the results of trade cooperation between Korea and Vietnam after applying VKFTA (2016-2020), (2) to find some difficulties and (3) to offer suggestions for Vietnam to improve the efficiency of trade relations with South Korea through a rudimentary SWOT analysis.Received 20th January 2023; Revised 10th March 2023; Accepted 5th April 2023